2023
DOI: 10.3390/antibiotics12040687
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Causative Microorganisms in Diabetic Foot Infections: A Ten-Year Retrospective Study in a Tertiary Care Hospital in Central Malaysia

Abstract: Diabetes mellitus is a global pandemic, especially in Southeast Asia. Diabetic foot infection (DFI) is a common complication of this condition and causes significant morbidity and mortality in those affected. There is a lack of locally published data on the types of microorganisms and empirical antibiotics being prescribed. This paper highlights the importance of local microorganism culture and antibiotic prescription trends among diabetic foot patients in a tertiary care hospital in central Malaysia. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…This system plays a crucial role in regulating various aspects, including biofilm formation and the expression of virulence factors such as toxins and degradative exoenzymes. Clinically, a study conducted at a central Malaysian tertiary care hospital indicated that Staphylococcus spp infections are associated with major amputations [45]. In a similar manner, DFU patients infected with Enterococci exhibited a significantly higher in-hospital amputation rate (72%) compared to those with non-Enterococci infections (50%) [27].…”
Section: Gram-positive Bacteriamentioning
confidence: 92%
See 4 more Smart Citations
“…This system plays a crucial role in regulating various aspects, including biofilm formation and the expression of virulence factors such as toxins and degradative exoenzymes. Clinically, a study conducted at a central Malaysian tertiary care hospital indicated that Staphylococcus spp infections are associated with major amputations [45]. In a similar manner, DFU patients infected with Enterococci exhibited a significantly higher in-hospital amputation rate (72%) compared to those with non-Enterococci infections (50%) [27].…”
Section: Gram-positive Bacteriamentioning
confidence: 92%
“…Most common Gram-negative bacteria include Pseudomonas aeruginosa, Escherichia coli, Klebsiella species, and Proteus species. Their prevalence differs according to geographical region [45][46][47].…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
See 3 more Smart Citations